Financial Feasibility Analysis of Broiler Chicken Traders at Korem Market, Mandonga District - Nurhayati, Siti; Sani, La Ode Arsad; Pagala, Muhammad Amrullah; Hadini, Hairil A; Surahmanto, Surahmanto; Sahaba, La Ode (Pascasarjana Universitas Halu Oleo, 2024)
Efforts to continuously improve in order to satisfy customers by maintaining good conditions for consumption. Based on the background, this study aims to analyze the financial level and feasibility of broiler chicken traders at Korem Market, Mandonga District. This research was conducted in January 2023 at Korem Market, Mandonga District, Kendari City. The research location was determined by purposive sampling, focusing on broiler chicken traders. Respondents were taken by census, including all broiler chicken traders who sell chickens daily at Korem Market, totaling 17 traders. Based on the research results, the average monthly income of broiler chicken traders at Korem Market is Rp2.400,795. The broiler chicken trading business is feasible to run, based on an R/C ratio of 1.05 and a B/C ratio of 0.05.